LESõES MUSCULOESQUELETICAS DECORRENTES DO TRABALHO EM FUNCIONáRIOS DE UM HOSPITAL PúBLICO (Fiep Bulletin - online, 2013)
This study aimed to identify muscle-skeletal pain related to work in a hospital environment, characterizing the regions most affected body and present risk factors for D.OR.T. The subjects understood 28 workers who were part of the sectors of nursing (post female, post male , Isolation, UTI general, pediatrics, maternity and first aid), catering, maintenance, laundry, cleaning and stretcher-bearer . We used a questionnaire containing questions related to musculoskeletal complaints. 95% of participants reported feeling some kind of musculoskeletal symptoms, the prevalence of such symptoms in anatomical areas were: lumbar region (44%), Brasil. Ministério da Saúde. Ato Portaria no19/GM de 03 de janeiro de 2002. [acessado em 30 de setembro 2008]. Disponível em: PORTARIAS/Port2002/Gm/GM-19.htm OLINTO, C. P.; OLIVEIRA M. P.; ZUARDI, M. H. M; BARROS, N. Grupos Educativos no Manejo de Pacientes Com Dor Crônica. Prática hospitalar 2005; 41. PESSINI, L. Humanização da dor e sofrimento humanos no contexto hospitalar. Bioética 2002; 10(2):51-72. http://dtr2001.saude.gov.br/sas/ http://www.scielo.br/scielo. Acesso em 01/10/2008 SMEDLEY, J; INSKIP, H.; COOPER, C; COOGON, D.Natural history of low back pain: a longitudinal study in nurses. Spine 1998; 23(22):2422-6. 151 FIEP BULLETIN Volume 79 - Special Edition - ARTICLE I - 2009 MMII (22%), MMSS (17%), thoracic region (12%). There was also, at that moment felt more ache (63% after the finish of work), posture to perform painful activity (53% of trunk flexion) and there were physical activity (64% reported not practice any type of physical activity). The results show that this poll is the high incidence of muscle-skeletal symptoms in multiple body regions, where the largest was ache in the lumbar region. There were also ergonomic factors related with back injuries, such as inadequate equipment, insufficient people to achieve changes in the supine position and transfers, inadequate stretchers, and others. Finally the importance of gym work associated with ergonomics that will contribute to improving the quality of life, creating spaces that break the pace and monotony of work seeking efficiency and health. Therefore, it is imperative the practice of preventive measures, such as the adequacy of furniture, physical activity and gym work.
Keywords: back pain; ergonomics; the hospital environment.